Drillstring Design in ERD Based on Torque and Drag Analysis using WellPlan - Ainin Nurfarahim Binti Hamdan, Ainin (Universiti Teknologi Petronas, 2012)
Directional drilling has long been considered as the backbone of most offshore drilling work. With the advancement of technology and increasingly difficult to reach reservoir, Extended Reach Drilling (ERD) has taken over as the opted solution. However, excessive torque and drag can impose critical limitations in ERD. This study aims to detail issues on DRILLSTRING DESIGN IN ERD BASED ON TORQUE AND DRAG ANALYSIS USING WELLPLANTM focusing on associated drilling problems- buckling and pipe sticking. The Landmark software which has been used for this study is developed by Halliburton and provides WELLPLANTM software that covers torque and drag analysis. The outcome of this study is further understanding on parameters governing torque and drag analysis with regards to drillstring design. This document is a dissertation report which encompasses the background of the study, a problem statement, the objectives, scope of study, the literature review, the research methodology, results, discussion, conclusion and recommendations. Keyword: Directional drilling; ERD; Torque and Drag; Drillstring Design; Landmark; Halliburton; analysis; optimization